Biomass and Chlorophyll Responses of Corn Plants (Zea mays L.) to Varying Abmix Concentrations in A Hydroponic Environment - Hidayatullah, Careca Sepdihan Rahmat; Priambodo, Okta Nindita; Sutanto, Oentari Prilaningrum; Arrasyid, Bagus (International Journal of Agriculture System, 2025)
Corn (Zea mays L.) is the second most important agricultural commodity in Indonesia, after rice. Corn plays an important role as a raw material for animal feed, bioenergy (biofuel), and various other industrial products. However, corn productivity is highly dependent on the availability of nutrients in the growing medium. Therefore, this study aims to evaluate the effect of various AB Mix concentrations on the biomass and chlorophyll of corn (Zea mays L.) plants in a hydroponic system. The experimental design used a simple randomized complete block design (RCBD) with one factor, namely the AB Mix concentration (1/2x, 1x, and 2x) and correlation analysis using R-Studio version 2025. At 6 WAP, differences in shoot, root, and total biomass between treatments were still significant. 2x AB Mix concentration again produced the highest biomass, namely 29.67 g. Variations in AB Mix concentration have a significant effect on biomass yield (biomass of shoots at 5-6 WAP, biomass of roots at 6 WAP, and total weight at 5-6 WAP) and chlorophyll a, b content, chlorophyll a+b ratio in corn leaves.